Stromal-associated cytokines bias the interplay between gene expression and DNA methylation in human breast cancers. Issue 5 (3rd May 2020) - Hernandez-Vargas, Hector; Goldsmith, Chloe; Mathot, Pauline; Dante, Robert
ABSTRACT: In human tumours, the crosstalk between cancer cells and their microenvironment is involved in tumour progression, metastasis and resistance to anti-cancer therapies. Among the factors involved in this exchange of information pro-inflammatory cytokines seem to play a crucial role. We observed that a group of pro-inflammatory cytokines, interleukin 6 (IL6), interleukin 1-beta (IL1b), and tumour necrosis factor-alpha (TNFa), preferentially activated genes exhibiting a high basal methylation level at their transcription start sites, in the human breast cancer cell line MCF7. In human breast tumours, these responding genes were also hypermethylated, and some of them (N = 104) were differentially methylated across human breast tumour samples (The Cancer Genome Atlas cohort). While their expression was positively correlated with the stromal content of the tumours and the expression of stromal-associated pro-inflammatory cytokines, the expression of this subset of genes was negatively correlated with their methylation level at their 5ʹ end. Nevertheless, while the methylation level of this subset of genes was not correlated with the stromal cell content of the tumours, this negative correlation was partially lost in tumours with high stromal cell content. Consistently, we observed that the methylation level in this subset of genes influenced the correlation between gene expression and stromal cell content. Thus, these data indicated that the stromal component of breast tumours should be taken into account for DNA methylation and gene expression studies and suggest an additional pathway, via DNA methylation, in the cross-talk between cancer cells and their microenvironment in human breast cancers.